2011
DOI: 10.1038/oby.2011.143
|View full text |Cite
|
Sign up to set email alerts
|

Orlistat 60 mg Reduces Visceral Adipose Tissue: A 24‐Week Randomized, Placebo‐Controlled, Multicenter Trial

Abstract: It is well established that abdominal obesity or upper body fat distribution is associated with increased risk of metabolic and cardiovascular disease. The purpose of the present study was to determine if a 24 week weight loss program with orlistat 60 mg in overweight subjects would produce a greater change in visceral adipose tissue (VAT) as measured by computed tomography (CT) scan, compared to placebo. The effects of orlistat 60 mg on changes in total fat mass (EchoMRI‐AH and BIA), ectopic fat (CT) and glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 33 publications
0
28
0
2
Order By: Relevance
“…There are some clinical studies with orlistat at 60 mg and 120 mg against placebo [3, 1214] in subjects undergoing caloric restriction for a period of treatment ranging between 14 and 104 weeks. These trials show that in general, an approximate weight reduction of about 2 kg can be added to weight loss induced by caloric restriction alone.…”
Section: Discussionmentioning
confidence: 99%
“…There are some clinical studies with orlistat at 60 mg and 120 mg against placebo [3, 1214] in subjects undergoing caloric restriction for a period of treatment ranging between 14 and 104 weeks. These trials show that in general, an approximate weight reduction of about 2 kg can be added to weight loss induced by caloric restriction alone.…”
Section: Discussionmentioning
confidence: 99%
“…51,55 The remaining 12 studies (2 studies were single-group pre-post designs, 1 study had a more active comparison group, and 9 studies reported outcomes at < 12 mo) were only included in analyses of adverse events. 24,29,57,63,[75][76][77][78][79][80][81]83 High within-group heterogeneity was common; however, the direction of treatment effect was consistent across most studies, and the confidence intervals overlapped. This statistical heterogeneity is likely due to small versus large treatment effects observed across studies.…”
Section: Resultsmentioning
confidence: 99%
“…20,27,57,59,61,66,67,[70][71][72][73]77,79,84 Gastrointestinal events were reported only in studies that used drug interventions and in the 23 studies with data that could be pooled; those taking active medications were more likely to report these events than control participants. 57,59,[61][62][63][64][65][66][67][68][69][71][72][73][74][75][76][77]79,[81][82][83][84] Likewise, participants in 25 pharmacologic studies were more likely to withdraw from their study because of adverse events compared with control participants (Table 5). 46,56,[58][59][60][61][62][63][64][65]…”
Section: Cmaj Openmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Swedish Multimorbidity Study, the authors concluded that treatment with orlistat in addition to dietary modifications produced significantly greater mean weight loss (5.9% in non-diabetics and 4.6% in diabetics) and CVD risk factor reduction than treatment with dietary modifications alone [44]. Weight loss with orlistat has been associated with improvement in comorbidities of obesity [45,46,47]. …”
Section: The Role Of Pharmacotherapy In the Treatment Of Obesitymentioning
confidence: 99%